Hubungan Umur Ibu dengan Kejadian Persalinan Prematur di Wilayah Kerja Puskesmas Kaliangkrik Kabupaten Magelang Tahun 2012 - Fatimah Sari; Evy Ernawati; Indartik Indartik (LPPM STIKES Guna Bangsa, 2014)
Background: One of the most common causes of death of neonates are low birth weight (LBW) either at term or preterm (premature). As a result of the premature births, children born will experience a variety of health problems due to lack of maturation of the fetus at birth which resulted in many organs of the body that have not been able to work perfectly. factors that can lead to preterm labor (preterm) or low birth weight infants is mother's first factor is less than 20 years of age or over 35 years . Method: This study aims to determine the relationship between maternal age with the incidence of preterm labor. Objective: This research is the type of observational analytic study with cross sectional approach. The sampling technique using saturated sample and the number of samples in this study were 75 respondents. Result: The results showed no association with maternal age on the incidence of preterm labor Puskesmas Kaliangkrik Magelang Regency in 2012 with a p value of 0.000 (0.000 < 0.05) and the relationship is strong enough that the value of the Contingency Coefficient .431. Conclusion: There is a relationship with the mother's age incidence of preterm labor.